Women Empowering Women Through Reusable Sanitary Pads - Naomi Lumutenga; Margaret Khaitsa; Ruth Muwazi; Florence Wakoko-Studstill; Irene Naigaga; Leslie Hossfeld; Margaret Ralston (The University of Alabama, 2022)
Menstrual Hygiene Management (MHM) is one of the top challenges for schoolgirls and female teachers in Uganda, leading to low retention rates for girls (25%) compared to boys (33%). One of Higher Education Resource Services-East Africa (HERS-EA) goals is to remove barriers to girls' education and advance women in leadership. This paper summarizes results of a community engagement project that trained rural women in two districts of Uganda (Bulambuli and Butaleja) in entrepreneurial skills and production of affordable reusable sanitary pads. Additionally, a needs assessment was conducted by HERS-EA. MHM issues and possible research areas (community education, engineering, environmental, business and marketing of sanitary pads) were identified. The paper highlights the plight of schoolgirls and rural women regarding MHM and the need for affordable sanitary pads to keep girls in school. The paper further highlights the mutual benefits of collaboration and opportunities that support university primary missions of education, research, and outreach.